Study on acceptance of immediate postpartum intrauterine contraceptive device and their follow-up - K., Fathima Banu; Nair, Atmaja; S., Jayasree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: India faces a persistent challenge with a high unmet need for family planning, particularly in the immediate postpartum period, with 65% of women in the first-year postpartum requiring contraception. Immediate postpartum intrauterine contraceptive devices (PPIUCDs) offer a highly safe, effective, long-acting, and reversible method that does not interfere with breastfeeding. This study aimed to determine the acceptance rate of PPIUCD, identify key factors influencing acceptance, and analyse reasons for discontinuation among postpartum women in a tertiary care centre. Methods: A study was conducted on 1,000 postpartum participants at Government Medical College, Kozhikode. Participants were counselled on PPIUCD (Cu T 380A), and acceptance, demographics, and follow-up data were collected at 6 weeks and 6 months postpartum. Results: The overall acceptance rate was 18% (n=179). Acceptance was significantly higher among parity 2 women (23.5%). Key reasons for acceptance included long-term use (41%) and reversibility (23%). The main reasons for rejection were fear of pain and bleeding (33%) and partner refusal (29.7%). At the 6-week follow-up, the continuation rate was 87%. Discontinuation (13%) was due to removal or expulsion. Conclusions: PPIUCD acceptance remains low but is significantly influenced by parity, age, and counselling location. Targeted, culturally sensitive counselling is essential to address common misconceptions and partner concerns to improve the uptake of this highly effective contraceptive method.